1967
DOI: 10.1056/nejm196701052760107
|View full text |Cite
|
Sign up to set email alerts
|

Fat Transport in Lipoproteins — An Integrated Approach to Mechanisms and Disorders

Abstract: Health was the first systematic treatment of abnorinalities in lipoprotein metabolism and fat transport. In addition to reiterating principles, they reported a simplified technology for measuring lipoproteins thut mu& these new formulations applicable to clinical medicine. Finally, they proposed u syAtem qj' management for the hyperlipoproteinemic phenotypes that was primarily nutritionid. HYPERLIPOPROTEINEMIA Definitions * * *Attention will be paid to practical steps to diagnosis and conservation therapy suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
198
0
31

Year Published

1968
1968
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,363 publications
(238 citation statements)
references
References 80 publications
9
198
0
31
Order By: Relevance
“…Vitamin E transiently present in chylomicrons following meals and in the serum is associated with beta-lipopro tein (30). It has been reported that vitamin E is virtually absent from the serum of patients with abetalipoproteinemia (31).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E transiently present in chylomicrons following meals and in the serum is associated with beta-lipopro tein (30). It has been reported that vitamin E is virtually absent from the serum of patients with abetalipoproteinemia (31).…”
Section: Discussionmentioning
confidence: 99%
“…Using the measured value of a2, al oc (a2ka4plu4) -1 (17) or, using the continuity equation, 1 1 (d\ 8 ka 4p2 U3D kD,/ From Eq (18) we can determine several interesting results. The constant a, is inversely proportional to the sound intensity.…”
Section: )mentioning
confidence: 99%
“…In our hands the coefficient of variation for replicate assays of triglycerides in a quality control sera was 2 96%, and for estimations carried out on different days was 310%. Lipoprotein electrophoresis was carried out on cellulose acetate by the method of Postma and Stroes (1968) and the abnormalities were classified according to the system of Fredrickson et al (1967). The upper limit of normal for plasma cholesterol was taken as 280 mg/100 ml and for plasma triglyceride as 2-0 mmol/l.…”
Section: Methodsmentioning
confidence: 99%